Eat Healthy “Organic” Food to be Healthy (Global Journal of Medical Research, 2023)
The article underlines the advantages of the so-called organic food grown with organic fertilizers caw horse or chicken manure It is rich of vitamins and minerals and has better taste and flavor The food raised with artificial fertilizer is mostly water and is low on vitamins and minerals Interestingly enough just as healthy as the organic food is the food grown with classical music as a stimulant instead of fertilizer - it has a good taste and flavor and it is rich of vitamins and minerals Unfortunately classical music was not accepted as a stimulant regardless of its eminent success because we were not understanding how it works According to my lifelong study of the aura the aura is emotionally sensitive it is brighter at positive emotions and dimmer at negative emotions This article explains that music influences the emotional aura of all living beings humans animals and plants My studies found that the aura is weak field but it rules and regulates the processes in all living beings It does this not with its strength but with the information it carries and music by influencing the emotional aura influences the whole development of the plants
Keywords: “organic” food; artificial fertilizers; organic fertilizers; music stimulates plant growth; explaining the effect of music